Filsafat dan Konsep Negara Marxisme - Permata, Harsa (Jurnal Filsafat "WISDOM", 2011)
Marxism is an ideology that based on dialectical and historical materialism philosophy. According to Marxism philosophy, matter is the mode of production in society. Marxism concept of dialectic is different from Hegelian. While the Hegelian dialectic is based on idea or spirit, Marxism dialectic is based on motion of matter as the mover of dialectics. In every process of dialecticsÂ there are contradictions that always exist. Communist society is the end of the historical dialectical society. Communist society will exist in reality after the withering away of the state because the state, according to Marxism philosophy, is a manifestation of class antagonism.Keywords: Marxism, dialetic, matter, contradiction, capitalism, communism.